An approach to enhance security awareness on the use of mobile devices - Sabeeh, Ahmed A. (2010)
The rapid development of mobile devices technology has turned them into real contenders and serious replacements for personal computers. On the other hand, this development has raised the number of attacks and security risks associated with the use of mobile devices. Mobile devices lack adequate protection in addition to the misuse of end-users. This study proposes a mobile devices security users’ security awareness framework. The framework was built based on an intensive review to security issues related to mobile devices, as well as the security awareness level among users. The framework consists of four variables namely; security knowledge, internet and services, privacy and updates and users’ attitudes. The data was collected through a quantitative method. The study has involved textual data and a survey questionnaire. The survey questionnaire was conducted in (UTM International Campus) including both students and staff as respondents in a try to reach a various number of mobile users. The results of this questionnaire came in contact with what was found in previous studies and indicated a significant weakness in users’ security awareness regarding mobile devices. Furthermore, the current security countermeasure, if found are not widely deployed due to the inconvenience they cause. The study has concluded that developing countermeasures alone without training users might not produce the secure environment required. This highlight security awareness and training as important factors to increase mobile devices’ security. Further work is necessary to develop practical guidelines in contact with NIST SP800-124 user oriented measures.